Behavior of the extramural uterine arteries in crossbred dogs (Canis familiaris - Linnaeus, 1758) - Freitas, Patrícia Maria Coletto (2002)
The present study involved thirty femeale adult dogs coming from the kennel of the Veterinary Hospital of the Federal University of Uberlândia, Minas Gerais, Brazil. The thoracic cavity of the animal was opened and the aorta astery (thoracic part) was locared and canulated. A 450 Neoprene latex solution was used to injet the aorta astery in caudal direction. The specimens were then fixed in a 10 % formol aqueous solution. The results showed that the ovaric, uterine and vaginal arteries supply the uterus as follows : (1) the ovaric artery, in all the cases, arose from the aorta artery, either cranially to the caudal mesenteric artery (98,33%) or at same level of this artery (1,67%). In 83,33% of the cases, it gave off a branch to the uterine corns, which was distributed on the dorsal (8,00%), on the ventral (12,00%) and ond the both (80,00%) surfaces. In addition, two uterine branches distributed on the ventral (66,67%) and the dorsal (33,33%) surfaces were found in 10,00% of the cases; (2) the uterine artery, in all the cases, arose from the vaginal artery. In all the specimens the artery uterine supplied the uterine corns, with the ventral surfaces receiving greater mean number of branches than the dorsal surface. Concerning the uterine body the mean number of branches from the uterine artery showed to be greater on the dorsal surface. In 70, 00% of the cases, the uterine cervix received branches from directly from the uterine artery, with greater number of these arterial vessels being found on the ventral surface.